Mother O'Neill : widow of the Kimberley goldfield - Coate, Yvonne E. ([Carlisle, W.A.] : Hesperian Press, 2012)
Sarah O'Neill was a widow on the Kimberley goldfield at the same time as Russian Jack (the famous 'wheelbarrow man' who became legendary throughout most Western Australia goldfields). Sarah led an even more fascinating existence in Halls Creek.
Cover title.
"Mother O'Neill : widow of the Kimberly goldfield"--Title page.
Includes bibliographic references (p. 134)
Keywords: O'Neill, Sarah; Women pioneers -- Western Australia -- Kimberley -- Biography; Pioneers -- Western Australia -- Kimberley -- Biography; Gold mines and mining -- Western Australia -- Kimberley -- History; Settlement and contacts - Settlers; Race relations - Violent; Sites - Mortuary sites and cemeteries; History - Biographies - Non-Indigenous.; History - Genealogy and family history; Brockman (East Kimberley WA SE52-01); Halls Creek (WA East Kimberley SE52-10); Hells Gate (WA East Kimberley SE52-09); Australian